Pričinnyj kompleks propagandy terrorizma - Vasilishyn, Valerii (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article examines the causes of terrorism and terms of propaganda.It analyzes the main conceptual approaches to the understanding of terrorism and its determination in individual criminal manifestations.The problem of determination of crime is the central problem in criminology, which still has not found a clear scientific solutions because of many objective and subjective factors. Determinism and causality are related, but not identical concepts. Criminological determination is a kind of social determination. A mechanism of determination includes different functions and implications: causes and conditions correlatives. Determinism expresses any conditionality of phenomena, objects, processes, all kinds of links between them.The reason points to a genetic link of the consequences and a particular cause as the main factors for its occurrence. By analysis of determination of crime criminogenic factors of terrorism propaganda were clarified.It was indicated that these factors determine the causal complex of terrorist propaganda in the form of a three-level pyramid. There were formulated causes and terms of terrorism propaganda, and determined deep, basic and current causes of terrorism propaganda. Within the classification of reasons of the terrorist propaganda were highlighted: the geopolitical, ideological, socio-economic, socio-psychological and organizational factors.
Keywords: terroryzm; przestępstwo; determinanty; przyczynowość propagandy terrorystycznej; działania terrorystyczne